2017
DOI: 10.1177/1533034617742301
|View full text |Cite
|
Sign up to set email alerts
|

Is Hippocampal Avoidance During Whole-Brain Radiotherapy Risky for Patients With Small-Cell Lung Cancer? Hippocampal Metastasis Rate and Associated Risk Factors

Abstract: Objectives:Hippocampal avoidance during whole-brain radiotherapy is performed to prevent neural stem cell injury causing neurocognitive dysfunction. Nevertheless, the estimated risk of metastases in hippocampal avoidance area in small-cell lung cancer is unknown. The current study aimed to characterize the metastatic distribution within the brain relative to the hippocampus, estimate the incidence of hippocampal metastasis in patients with small-cell lung cancer, and identify clinical and radiographic variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Dose to hippocampi could be minimised if the PTV locates far from the hippocampi. In Korkmaz Kirakli and Oztekin (2017) study, the distance between multiple brain metastases and hippocampi were measured to evaluate the risk of recurrence after whole brain radiotherapy 28 . While in this study, primary single tumour was treated.…”
Section: Discussionmentioning
confidence: 99%
“…Dose to hippocampi could be minimised if the PTV locates far from the hippocampi. In Korkmaz Kirakli and Oztekin (2017) study, the distance between multiple brain metastases and hippocampi were measured to evaluate the risk of recurrence after whole brain radiotherapy 28 . While in this study, primary single tumour was treated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrate that sparing the hippocampus from radiation without altering the coverage of the rest of the brain decreases early NCF decline without compromising disease control. Dosimetric studies utilizing various techniques to spare the hippocampus including both intensity modulated radiotherapy (IMRT) and helical TomoTherapy treatment first demonstrated the feasibility of hippocampal avoidance during WBRT 9–13 . RTOG 0933 was a multi‐institutional phase II trial of HA‐WBRT for brain metastases 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the metastasis rate of SCLC in the hippocampus is approximately 3–5.1% [ 10 13 ]. Modern radiotherapy modalities include conventional three-dimensional conformal radiation therapy (3D-CRT) and intensity-modulated radiation therapy (IMRT) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%